2021
DOI: 10.2196/27539
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Measurement Tools for Assessing Health Information–Seeking Behaviors in Nationally Representative Surveys: Systematic Review

Abstract: Background The coronavirus pandemic (COVID-19) has also emerged as an infodemic, thereby worsening the harm of the pandemic. This situation has highlighted the need for a deeply rooted understanding of the health information–seeking behaviors (HISBs) of people. Objective The aim of this paper was to review and provide insight regarding methodologies and the construct of content in HISB surveys by answering the following research question: what are the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…This tool has been continuously adapted to the phases of the pandemic [ 53 ]. A recent review highlights how these tools have gradually been used in different countries during the pandemic [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tool has been continuously adapted to the phases of the pandemic [ 53 ]. A recent review highlights how these tools have gradually been used in different countries during the pandemic [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown how the restrictions could cause psychological problems, including anxiety. In line with the solutions proposed in [ 53 , 54 ], we developed an electronic survey to investigate this. The part of the survey dedicated to the anxiety test made it possible to highlight, as a first important and troubling result, the very high anxiety prevalence rate (23.1%) among the youths during the COVID-19 outbreak in line with other studies [ 33 , 35 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The infodemic worsened the impact of the pandemic and led to damage and harm [33,42]. Fake news, conspiracy theories, and racist news might even lead to loss of life [32,42]. Likewise, unscientific and unproven cures were harmful [21].…”
Section: Harmmentioning
confidence: 99%
“…Capturing the risk perception and risk competence can identify gaps in the population and support crisis preparation [20]. A good understanding of health information seeking behavior of the population can help mitigating and preparing for an infodemic [42]. Scientists play a significant role in the context of an infodemic because of their expertise and their societal standing; they should be conscious about this and be prepared to respond to families, friends, and the community [17].…”
Section: Pre-impact Measuresmentioning
confidence: 99%
See 1 more Smart Citation